Advances in Molecular Imaging with Ultrasound - Ryan Gessner; Paul A. Dayton (Molecular Imaging)
Ultrasound imaging has long demonstrated utility in the study and measurement of anatomic features and noninvasive observation of blood flow. Within the last decade, advances in molecular biology and contrast agents have allowed researchers to use ultrasound to detect changes in the expression of molecular markers on the vascular endothelium and other intravascular targets. This new technology, referred to as ultrasonic molecular imaging, is still in its infancy. However, in preclinical studies, ultrasonic molecular imaging has shown promise in assessing angiogenesis, inflammation, and thrombus. In this review, we discuss recent advances in microbubble-type contrast agent development, ultrasound technology, and signal processing strategies that have the potential to substantially improve the capabilities and utility of ultrasonic molecular imaging.